The Effect of Self-Congruity on The Loyalty of Young Domestic Tourists in Bali Through Destination Personality - Dewi, Ni Gusti Ayu Susrami; Wulandani, Ni Luh Kadek Laksmi (Jurnal Internasional Riset Bisnis Pariwisata, 2025)
This study focuses on the loyalty of young domestic tourists to Bali as a tourist destination. The loyalty of this segment is important to examine because young domestic tourists represent both a potential and actual market for Bali. Strong loyalty among young tourists can generate various positive impacts, including reduced promotional costs, sustained profitability, and an enhanced positive image of Bali as a destination. Considering the unique characteristics of young tourists—who tend to seek novel and authentic experiences—this study identifies key determinants such as self-congruity, destination personality, and tourist loyalty. Employing an explanatory research design with a mixed-method approach integrating quantitative and qualitative components, and using Multiple Linear Regression for the quantitative analysis, the study offers in-depth insights into how self-congruity and destination personality influence loyalty. Tourist loyalty in this research is measured through revisit intention and recommendation intention. This study is particularly relevant due to the limited existing research on the loyalty of young domestic tourists toward Bali. The results of the Multiple Linear Regression (mediation) analysis show that self-congruity has a significant positive effect on destination loyalty and tourist loyalty. Destination personality also has a significant positive effect on loyalty. Furthermore, the analysis reveals that Destination Personality partially mediates the relationship between Self-Congruity and Tourist Loyalty significantly.